Emotional reactivity to grief-related expressive writing. Issue 9 (1st September 2020) - Rubin, Mikael; Hawkins, Baylee; Cobb, Adam; Telch, Michael J.
Abstract: The efficacy of expressive writing for bereavement remains unclear, although some evidence suggests that writing about positive memories of one's loved one may be particularly beneficial. The current pilot study compared the effects of a brief positive expressive writing intervention for enhancing positive affect among bereaved adults ( N  = 403). Participants were randomly assigned to write about a positive memory of the deceased person or recent neutral activity. Results revealed no main effect of the positive writing condition on mood change. However, greater positive emotion word use mediated positive affect among those in the positive writing condition.